Pengaruh Kebijakan Manajemen SDM: Studi Model Kebijakan Rekrutmen, Seleksi dan Penempatan Karyawan terhadap Efektivitas Kinerja PT. Perkebunan Nusantara III - Sri Devita Purba; Dhita Adriani Rangkuti; Yelsina Sitanggang; Wilson Z. Simbolon; Bena Br Ginting (Universitas Batanghari Jambi, 2023)
PT Perkebunan Nusantara III or often called PTPN III (Persero) is a State-Owned Enterprise engaged in the management, and processing of plantation products such as Palm Oil, Rubber, Sugar Cane, Tea, Coffee, Cocoa, Tobacco, and several other plants that are also produced by PTPN. The problem underlying this research is whether the recruitment, selection, job placement policies simultaneously and partially affect and are significant to the effectiveness of performance at PTPN III. The method used is quantitative method, while the data collection techniques in this study were carried out by questionnaire and distributing questions to respondents as many as 82 respondents, From the results of the F test simultaneously Recruitment, Selection, and Placement of Employees tested have an effect and are significant to the effectiveness of performance. Partial Test (t-test) shows that partially the variables of recruitment, selection, placement of employees have an effect and are significant to the effectiveness of performance at PTPN III. While in the Determination Test the amount of adjusted R square is 0.172 (17.2%), while the remaining 82.8% (100% - 17.2%) is explained by other variables not examined in this study.